The design of a high-performance, floating-point embedded system for speech recognition and audio research purposes - Duckitt, William (Stellenbosch : Stellenbosch University, 2008)
Thesis (MScEng (Electrical and Electronic Engineering))--Stellenbosch University, 2008.